ANALISIS PENGARUH RASIO KEUANGAN,, MARKET VALUE ADDED (MVA) DAN ECONOMIC VALUE ADDED (EVA) TERHADAP HARGA SAHAM (Sttudii Kasus pada Perusahaan Properttii dii Bursa Efek Indonesiia Tahun 2005-2009) - , Rahmawati, S.E. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Financial ratio is the instructions to find out how the performance and financial condition of a company acquired by analyzing financial statements. However, the performance measurement that only analyze the financial statements have major weaknesses which disregard the cost of capital, so it is difficult to know whether a company has managed to create the value for the market and the owners of capital, then to overcome these weaknesses, itâs developed the concept on Market Value Added (MVA) and Economic Value Added (EVA). This research aims to analyze the effect of financial ratios, Market Value Added (MVA) and Economic Value Added to the stock price. The cases studies on property companies listed on the Indonesian Stock Exchange 2005-2009 period. This research sample consist of 14 companies and use the five (5) financial ratios include: Current Ratio (CR), Return On Assets (ROA), Return On Equity (ROE), Earning Per Share (EPS) and Debt to Equity (DTE). It is also add the variable Market Value Added (MVA) and Economic Value Added. Statistical method used in this research was multiple regression with panel data. The research result shows that simultaneously the independent variables have a significant effect on the stock price. All the independent variable only can explain the variations in stock prices of about 63,60% and the valance of 36,40 persen is explained by other variables outside the model